Pengaruh Metode Card Sort Terhadap Hasil Belajar Ipas Materi Pengelompokan Mahluk Hidup Di Kelas V MI NW Lenek - Johan Efendi; Lalu Fauzi Haryadi; Muh. Thala’at (Yayasan Azhar Amanaa Yogyakarta, 2026)
This research is motivated by the low learning outcomes of students in IPAS subjects, particularly in the topic of classifying living things, which is caused by the predominance of lecture-based teaching methods that tend to make students passive. The purpose of this study is to examine the effect of the Card Sort method on the IPAS learning outcomes of fifth-grade students at MI NW Lenek. This study employs a quantitative approach using a Quasi-Experimental method with a Nonequivalent Control Group Design. The sample consists of 30 fifth-grade students, divided into an experimental group (15 students) and a control group (15 students), selected through purposive sampling. Data collection was conducted using a multiple-choice test instrument that had previously undergone validity and reliability testing. The data analysis techniques include normality tests, homogeneity tests, and the Independent Sample T-Test. The findings reveal that the average posttest score of the experimental group (67.73) is significantly higher than that of the control group (38.53), with an improvement gain of 39.46. The hypothesis testing indicates a significance value of < 0.001 (α = 0.05) and an effect size (Cohen’s d) of 2.532. These results demonstrate that the Card Sort method has a positive effect and a very strong impact on improving students’ learning outcomes.